Consolidating facts and redesigning a novel pediatric dental practice in nCOVID-19 pandemic - Khooshbu Gayen; Supreet Shirolkar; Sauvik Galui; Subrata Saha; Subir Sarkar (Wolters Kluwer Medknow Publications, 2021)
The pandemic of coronavirus disease 2019 has been the most unprecedented event of our lifetimes, touching, and probably forever changing all realms of our lives and livelihoods. The field of general and speciality dental practice remains no exception. Among all health-care professionals, dentists as oral health caregivers are those who are most susceptible to contracting this infection. A never before situation like this has engaged all of humanity in studies and research for better understanding and possibly reducing the disaster that this terrible virus can inflict upon humanity. These efforts have led to a lot data, much of which is anecdotal evidence and thus a dire need to segregate facts has risen. Dentists in general and pediatric dentists in particular who routinely deal with children and managing them for dental care are at a heightened risk because of their job primarily in the oral cavity. Children routinely take longer appointments compared to adults and require more care to be exercised during this pandemic. This infection often presents asymptomatically which further complicates the problem. Thus, in a world that exists during and after this pandemic demands a reimagined dental practice that is safe for the health workers as well as effectively and efficiently delivers oral health care to all age groups. This can be achieved by rigorous and extensive study and consolidation of this knowledge which can then be adapted by health workers on the ground.